Analisis Strategi Pemasaran Usaha Garam terhadap Tingkat Pendapatan Petani Garam: (Studi Kasus di Kampung Garam Kelurahan Kota Uneng) - Intan Vidya Wati; Pipiet Niken Aurelia; Henrikus Herdi (Universitas 45 Surabaya, 2024)
The aim of this research is to determine and analyze the marketing strategies of salt farmers which consist of product, price, promotion and distribution strategies. The research location is in Garam Village, Uneng City Village, Alok District, Sikka Regency. Data collection techniques were carried out by direct observation, interviews and documentation. Data analysis was carried out descriptively-qualitatively. The analysis results from the product strategy side show that 1). The raw material for making salt is abundant sea water, 2). The quality of traditional salt farmers' salt products is considered very far from good quality, 3). Farmers do not create and own trademarks. From the price strategy side it appears that 1). The determinants of price policy are the middlemen and follow market prices, 2). Cash payment system at the time of transaction or by deferring in advance or being paid by the buyer. From the promotional model side, it can be seen that 1). Farmers do not have promotional tools, 2). The farmers feel that there has never been any party or anyone to help promote their production to the general public, and in terms of distribution strategy it has been found that 1), the dominant farmers sell their salt production to middlemen, and 2). Some are sold in traditional markets.